An Exploratory Analysis of Fifteen Years Suicide Trends Using Population-Level Data From Croatian Committed Suicides Registry - Pajić, Vanja; Orešković, Stjepan (Frontiers in Public Health, 2022)
Objectives The provide a descriptive analysis of the available population-level aggregated data on committed suicides in the Republic of Croatia, in the 2004–2018 period, showing emerging trends in suicide incidence focusing on sex/age/geographical distribution of suicides and the primary and secondary causes of suicide mortality, as well as making comparisons with similar neighboring neighboring countries. Methods The aggregated suicide data were obtained from the Croatian Committed Suicides Registry, a national registry maintained by the public health authority. The raw data extract was organized into tables according to several variables (age, sex, place of birth, place of residence, and cause of death). Simple descriptive statistics were performed on the structured data. Results Despite being among the highest in the world and EU, the number of committed suicides in Croatia is in decline since 2004. A higher number of suicides by males was observed when compared to females. Most of the suicides occur during spring and summer. The wealthier, northern continental region of the country had the highest average rate of committed suicides per 1,00,000 population, contrary to some of the findings in the published literature associating economic instability with suicide. The most common way to commit suicide for both sexes in all age groups is self-harm by hanging, strangulation and suffocation. Suicide by firearm and explosive devices discharge remains higher than the global average. Conclusions Despite its steadily declining incidence rates in the past 20 years, suicides remain a major public health challenge in Croatia. Results may bolster the Ugro-Finnish suicide hypothesis, linking higher suicide rates to regions with populations of Hungarian descent.